Fear of Missing Out (FoMO) and social media's impact on daily-life and productivity at work: Do WhatsApp, Facebook, Instagram, and Snapchat Use Disorders mediate that association?. (November 2020) - Rozgonjuk, Dmitri; Sindermann, Cornelia; Elhai, Jon D.; Montag, Christian
Highlights: FoMO correlated positively with social media's (negative) impact on daily-life and productivity. FoMO correlated with WhatsApp, Facebook, Instagram, and Snapchat Use Disorders (UDs). WhatsApp, Facebook, and Instagram UDs mediated FoMO's link with social media's negative impact. Snapchat UD was not a significant mediator. Abstract: Fear of Missing Out (FoMO) is the tendency to experience anxiety over missing out on rewarding experiences of others. It has been associated with daily-life disruptions, such as distractions during driving. FoMO has also consistently been a predictor of Internet, smartphone, and social networks use disorders. In the current work, we investigated the association between FoMO and social media use's impact on daily-life and productivity at work. In addition, we aimed to determine whether WhatsApp, Facebook, Instagram, and Snapchat Use Disorders mediate that relationship. The effective sample comprised 748 German-speaking study participants from the general population (age M = 38.63, SD = 12.10; 336 men, 412 women) who took part in an online survey study. Bivariate analyses showed that severity of all social networks use disorders were positively correlated with FoMO and social media's negative impact on daily-life and productivity at work. Furthermore, controlling for age and gender, mediation analyses showed that out of all platforms, only Snapchat Use Disorder did not mediate the association between FoMO and social media's negative impact on daily-life and productivity at work. These results provide further evidence about FoMO's central role in digital technology use-related disorders.